1998
DOI: 10.1104/pp.118.3.997
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects on Spodoptera littoralis Larvae of High Expression Level of a Trypsin Proteinase Inhibitor in Transgenic Plants

Abstract: This work illustrates potential adverse effects linked with the expression of proteinase inhibitor (PI) in plants used as a strategy to enhance pest resistance. Tobacco (Nicotiana tabacum L. cv Xanthi) and Arabidopsis [Heynh.] ecotype Wassilewskija) transgenic plants expressing the mustard trypsin PI 2 (MTI-2) at different levels were obtained. First-instar larvae of the Egyptian cotton worm (Spodoptera littoralis Boisd.) were fed on detached leaves of these plants. The high level of MTI-2 expression in leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(62 citation statements)
references
References 39 publications
(20 reference statements)
1
59
0
2
Order By: Relevance
“…Serine proteases provide the major midgut endoproteolytic activities in S. littoralis larvae [34], and previous studies have demonstrated that transgenic plants expressing serine protease inhibitors can confer resistance against S. littoralis [45], [46]. When the protease inhibitor AtSerpin1 was incorporated into an artificial diet, the weight gain of S. littoralis larvae was substantially reduced relative to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Serine proteases provide the major midgut endoproteolytic activities in S. littoralis larvae [34], and previous studies have demonstrated that transgenic plants expressing serine protease inhibitors can confer resistance against S. littoralis [45], [46]. When the protease inhibitor AtSerpin1 was incorporated into an artificial diet, the weight gain of S. littoralis larvae was substantially reduced relative to the control.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for such observations is the presence in phytophagous insects of a variety of mechanisms that counter adverse effects of plant proteinase inhibitors. The simplest mechanism involves increasing the secretion of the proteinase sensitive to the inhibitor [316]. Alternatively, the inhibitor may be cleaved by those intestinal proteinases that are resistant to it [317,318].…”
Section: Physiological Functionsmentioning
confidence: 99%
“…Available molecular and biochemical studies have revealed several diverse strategies used by insect herbivores. They may (1) overproduce the existing digestive enzymes to ‘titre out’ the inhibitors (De Leo et al ., 1998); (2) express different enzymes, which are insensitive to the protease inhibitors (Bolter & Jongsma, 1995; Jongsma et al ., 1995; Bown et al ., 1997; Cloutier et al ., 2000; Mazumdar‐Leighton & Broadway, 2001); or (3) activate expression of hydrolysing enzymes that fragment the inhibitors (Michaud et al ., 1995; Giri et al ., 1998). Cowpea bruchids apparently are able to employ all three of these strategies when challenged by dietary scN at a dosage level equivalent to the natural plant defence response when attacked by insect herbivores (Zhu‐Salzman et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%